Hubungan Komunikasi, Motivasi Kerja Dan Etos Kerja Guru dengan Kinerja Guru Sekolah Dasar Negeri di kecamatan Tambang Ulang Kabupaten Tanah Laut - Rahmat Alfian Madani; Metroyadi Metroyadi; Ahmad Muhyani Rizalie (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research aims to analyze the relationship between Communication, work motivation, and work ethic on the performance of state elementary school teachers in Tambang Lagi District, Tanah Laut Regency. This research is correlational research with descriptive-quantitative methods. The research population consisted of 138 public elementary school teachers in Tambang Re District, Tanah Laut Regency, with a sample size of 103 respondents who were taken using random sampling techniques. Data collection uses questionnaire instruments, and data analysis uses descriptive analysis, classical assumption tests, multiple linear regression analysis, and path analysis. The results of the research show that there is a relationship between Communication on teacher performance 0.658, work motivation on teacher performance 0.547, work ethic on teacher performance 0.879, Communication on work ethic 0.292, (5) work motivation on work ethic 0.484, Communication through work ethic on teacher performance is 0.257, work motivation through work ethic on teacher performance is 0.425. The coefficient of determination test results show that the R Square value of the job satisfaction variable is 0.886. In conclusion, the variables of Communication, work motivation, and work ethic influence teacher performance, while communication and work motivation influence teacher performance. Keywords: Communication, Teacher ¸Work Motivation, Work Ethic